2018
DOI: 10.1016/j.schres.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the rewarding and aversive associative properties of nicotine in the neonatal quinpirole model: Effects on glial cell line-derived neurotrophic factor (GDNF)

Abstract: This study analyzed the associative properties of nicotine in a conditioned place preference (CPP) paradigm in adolescent rats neonatally treated with quinpirole (NQ) or saline (NS). NQ produces dopamine D receptor supersensitivity that persists throughout the animal's lifetime, and therefore has relevance towards schizophrenia. In two experiments, rats were ip administered quinpirole (1mg/kg) or saline from postnatal day (P)1-21. After an initial preference test at P42-43, animals were conditioned for eight c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…One weakness of the current study is that we did not include animals that were socially housed, but all of our past work in the NQ model has been in socially housed rats. For example, in recent work [53], we reported that socially housed animals conditioned to nicotine in the CPP behavioral paradigm administered a slightly higher dose (0.6 vs. 0.5 mg/kg free base used in the present study) did not produce an increase of GDNF in the NAcc, although there were increases in NAcc GDNF in NQ-treated rats given nicotine, similar to the effects observed here. In the current study, it appears that enrichment has a particularly robust effect on accumbal GDNF in NQ-treated animals that does not appear to be influenced by nicotine, whereas nicotine may interact with housing condition in a presumably different way to influence accumbal GDNF in NS-treated rats.…”
Section: Discussionsupporting
confidence: 88%
“…One weakness of the current study is that we did not include animals that were socially housed, but all of our past work in the NQ model has been in socially housed rats. For example, in recent work [53], we reported that socially housed animals conditioned to nicotine in the CPP behavioral paradigm administered a slightly higher dose (0.6 vs. 0.5 mg/kg free base used in the present study) did not produce an increase of GDNF in the NAcc, although there were increases in NAcc GDNF in NQ-treated rats given nicotine, similar to the effects observed here. In the current study, it appears that enrichment has a particularly robust effect on accumbal GDNF in NQ-treated animals that does not appear to be influenced by nicotine, whereas nicotine may interact with housing condition in a presumably different way to influence accumbal GDNF in NS-treated rats.…”
Section: Discussionsupporting
confidence: 88%
“…GDNF is a glial cell derived neural growth factor. Increased GNDF has been reported to play a role in colon cancer metastasis and colon cancer cell migration; it also plays a role in other cancers 42 including head and neck cancer 16 , and is influenced by smoking behavior 43 , 44 . We found decreased methylation of cg18121355 in TCGA samples of heavy smokers compared to those collected form never smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The latter action of nicotine was blocked by the nicotinic receptor antagonist mecamylamine (Tizabi et al, 1999). In addition, rats that were neonatally quinpirole-primed have shown increased behavioral sensitization to nicotine (Sheppard et al, 2009;Perna and Brown, 2013), conditioned place preference to nicotine (Brown et al, 2018), and enhanced DA (Perna and Brown, 2013) and brain-derived neurotrophic factor responses to nicotine (Peterson et al, 2017) in the NAC, a brain area that mediates drug reward. All these findings are consistent with the hypothesis that a D 2 RSS system is enhanced in its sensitivity to the rewarding aspects of nicotine.…”
Section: Production Of Da D 2 Rss: Neurochemical and Behavioral Effecmentioning
confidence: 99%